Deep throat diva : a novel - Cairo (New York : Strebor Books, 2011)
"With brains, beauty, and a four-carat diamond engagement ring, Pasha Willow seems to have the perfect life. She's the successful owner of a trendy hair salon, lives in a posh condo with her handsome soon-to-be husband, drives an expensive care, and indulges in relentless shopping sprees. But behind the high-end fashion, captivating smile, and mesmerizing eyes, belies [sic] a woman with a deep, dark secret." --p. [4] of cover.
At head of title: Zane presents
Keywords: African Americans -- Fiction; Erotic stories